Sacrificers (2023), volume 1 ebook - Remender, Rick (Sacrificers (2023), 2024)
Tomorrow is a harmonious paradise thanks to five families who make everything perfect...for the price of one child per household. Now, as that bill comes due, a son expected to give everything for a family that never loved him and an affluent daughter determined to destroy utopia must unite to end one generation's unnaturally protracted reign. The first chapter of the new hit series by superstar creators RICK REMENDER and MAX FIUMARA! Collects THE SACRIFICERS #1-6